Alzheimer’s Disease and the Amyloid Cascade - Oliveira, Isadora Cucolo; e Castro, Maitê de Mello; Consulin, Vitoria; Antunes, Gabriel Hiroaki; dos Santos, Tárik Abdalla; Lourenço, João Pedro Vayego; Covizzi, Ian Vilas Boas; Vayego, Sheila Adami; Lima, Alba Regina de Abreu; Covizzi, Uderlei Doniseti Silveira (Seven Editora, 2024)
Alzheimer’s disease is neurodegenerative and may have a sporadic characteristic, often associated with failures in proteostasis, related to the individual’s aging processes. It can also present a hereditary contribution, especially in cases where it appears early in patients. The amyloid cascade, which is mainly responsible for the development of the pathology, involves events of fragmentation of the amyloid precursor protein (APP) by peptidases known as beta and gamma secretases, generating an increased amount of a poorly soluble protein fragment, which is deposited in the interneuronal space, forming amyloid plaques. Physiological changes lead to structural changes in tau protein, a component of neuronal microtubules, which when hyperphosphorylated by cell kinases, aggregate to form neurofibrillary tangles. The progression of these protein deposits induces synaptic and neuronal loss, by activating glial cells that release pro-inflammatory cytokines, generating atrophy mainly in the hippocampus and cerebral cortex. The main treatments available so far to control Alzheimer’s disease are not very encouraging, since they do not act effectively on amyloidosis. More recent studies involve the production of monoclonal antibodies capable of interacting with protein fragments, breaking down these senile plaques. While they represent a significant advancement, it is important to consider the risks and potential side effects of these medications. DOI:https://doi.org/10.56238/sevened2024.016-023